2022
DOI: 10.3390/v14030449
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Effective Peptide-Based Vaccine for COVID-19: Preliminary Studies in Mice Models

Abstract: Coronavirus disease 2019 (COVID-19) has caused massive health and economic disasters worldwide. Although several vaccines have effectively slowed the spread of the virus, their long-term protection and effectiveness against viral variants are still uncertain. To address these potential shortcomings, this study proposes a peptide-based vaccine to prevent COVID-19. A total of 15 B cell epitopes of the wild-type severe acute respiratory coronavirus 2 (SARS-CoV-2) spike (S) protein were selected, and their HLA aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…While several types of vaccines have been developed to address the disease, the PBVs have not received as much attention. However, these vaccines have several potential benefits, including increased safety, immunogenicity, and cost-effectiveness ( Yang et al, 2022 ). Computational methods can be used to identify potential vaccine candidates more quickly and cost-effectively than traditional laboratory-based approaches ( Oluwagbemi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While several types of vaccines have been developed to address the disease, the PBVs have not received as much attention. However, these vaccines have several potential benefits, including increased safety, immunogenicity, and cost-effectiveness ( Yang et al, 2022 ). Computational methods can be used to identify potential vaccine candidates more quickly and cost-effectively than traditional laboratory-based approaches ( Oluwagbemi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, subunit/peptide-based vaccines are developed in which a small portion of pathogen protein is utilized in order to generate the vaccine candidates against [24,[51][52][53][54][55][56]. While designing a subunit-vaccines it is necessary to check the peptide/antigens have the capacity to effectively stimulate the immune system and generate specific type of cytokines to send signal to the immune system to perform inflammatory responses against the pathogens and cancerous In the current study, we have used experimentally validated IFN-γ inducing and non-inducing peptides from IEDB resource.…”
Section: Discussionmentioning
confidence: 99%
“…All examined mAbs were shown to bind to peptide #37 spanning the amino acids 444-458 (Figure 4B), located within the RBM [85]. It has been shown that this region includes human T cell epitopes with a capacity to induce T cell response in mice [207]. Following the identification of the immundominant epitope (mimotope #37, KVGGNYNYLYRLFRK), a vaccine compound consisting of the synthesized peptide conjugated to CRM197 (P#37-CRM197) was used in a prime-boost immunization experiment.…”
Section: B Cell Peptide/mimotope-based Vaccinementioning
confidence: 99%